The Impact of Firm-Generated and User-Generated Content on Brand Loyalty on TikTok: The Role of Trust and Engagement - Burhan; Listiana, Erna; Purmono, Bintoro Bagus; Afifah, Nur; Setiawan, Harry (Ilomata International Journal of Management, 2025)
TikTok, a leading social media platform with Indonesia as the world's second largest user (113 million active users). Speeds successfully utilized TikTok as a digital marketing strategy, recording sales of 12,733 seats with revenue of Rp 648.21 billion. The platform is effective because it facilitates authentic interactions between brands and consumers. This study seeks to analyze the unique effects of firm-generated content (FGC) and user-generated content (UGC) on brand loyalty inside a particular social media platform. This study specifically examines the relationship between FGC and UGC regarding brand loyalty for Speeds items on TikTok, while analyzing the mediating effects of brand trust and social media brand engagement (SMBE). The research has a quantitative design utilizing a survey methodology. A purposive sample of 217 respondents was obtained from active TikTok users. Data analysis was performed with AMOS 22 software and structural equation modeling (SEM). The findings demonstrate that both FGC and UGC significantly affect the development of social media brand engagement, hence enhancing brand loyalty. The mediating influence of brand trust reveals a more complex relationship that requires further examination. These results align with previous research highlighting social media content's crucial role in strengthening consumer-brand relationships, particularly in environments of heightened consumer engagement.